2005
DOI: 10.1016/j.envsoft.2004.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Human activities and global warming: a cointegration analysis

Abstract: Using econometric tools for selecting I(1) and I(2) trends, we found the existence of static long-run steady-state and dynamic long-run steady-state relations between temperature and radiative forcing of solar irradiance and a set of three greenhouse gases series. Estimates of the adjustment coefficients indicate that temperature series is error correcting around 5e65% of the disequilibria each year, depending on the type of long-run relation. The estimates of the I(1) and I(2) trends indicate that they are dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
9
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 47 publications
4
9
0
1
Order By: Relevance
“…We concluded that all four temperature time series are integrated of order one. These results are consistent with those obtained by Stern and Kaufmann ([24]), Liu and Rodriguez ( [25]) and Mills ([26]). Now, in order to build a model portfolio for the considered time series, we identify ARMA models for the first differences of our time series.…”
Section: An Empirical Applicationsupporting
confidence: 83%
“…We concluded that all four temperature time series are integrated of order one. These results are consistent with those obtained by Stern and Kaufmann ([24]), Liu and Rodriguez ( [25]) and Mills ([26]). Now, in order to build a model portfolio for the considered time series, we identify ARMA models for the first differences of our time series.…”
Section: An Empirical Applicationsupporting
confidence: 83%
“…Here, we take d max to be equal to 1. In fact, recent researches (Kaufmann and Stern, ; Stern and Kaufmann, ; Liu and Rodriguez, ; Kodra et al , ; Attanasio, ) show that global temperature has an integration order of 1. Attanasio (2012) finds the natural forcings, and GHG‐total RF are at most integrated of order 1.…”
Section: Resultsmentioning
confidence: 99%
“…Within the field of econometrics there exists an extensive body of literature on analysis of time series containing a combination of stochastic and deterministic trends. We find it peculiar that these analysis tools, which are applied on a routine-basis in economical analyses, are rarely applied in the analysis of climate data, with Stern (1997, 2002), Kaufmann et al (2006aKaufmann et al ( , 2006b), Liu and Rodriguez (2005), Mills (2009), Stephenson et al (2000), Stern (2006), Stern andKaufmann (1999, 2000) as notable exceptions. A central concept in these works is cointegration, which is also the backbone in the method we will apply.…”
Section: Introductionmentioning
confidence: 99%